Pandangan Martin Luther tentang Pembenaran oleh Iman dalam Yakobus 2:14-26 - Maria Payer; Antonius Missa; Bobby Kurnia Putrawan (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2022)
In this paper, the authors explain that the views of a reforming theologian named Martin Luther once stated that the letter of James "mangles the Scripture and thereby opposes Paul and all Scripture" and called this letter an epistle of straw. ' (straw letter). Luther's statement was prompted by his doubts about the letter of James, which emphasizes good works more than faith. Although James himself did not mean it that way, Luther's view has prompted many theologians who interpret James' teaching on faith and works specifically discussed in chapter 2 to contradict Paul's teaching of justification by faith alone in Christ (Rom 3:24,28). Here the authors discuss the reflection on Martin Luther's views with James 2:14-26 regarding justification by faith.AbstrakDalam tulisan ini, para penulis menjelaskan bahwa pandangan seorang teolog reformasi yang bernama Martin Luther pernah menyatakan bahwa surat Yakobus ini adalah ’’mangles the Scripture and there by opposes Paul and all Scripture’’ dan menyebut surat ini sebagai ’’an epistle of straw’’ (surat jerami). Pernyataan Luther ini didorong oleh keraguannya kepada surat Yakobus yang lebih menekankan perbuatan baik daripada iman. Meskipun Yakobus sendiri tidak bermaksud demikian, namun pandangan Luther ini  telah mendorong banyak teolog yang menafsirkan ajaran Yakobus mengenai iman dan perbuatan yang dibahas khusus dalam pasal 2 ini bertentangan dengan ajaran Paulus mengenai pembenaran hanya oleh iman kepada Kristus (Rm. 3:24,28). Disini  para penulis membahas refleksi pandangan Martin Luther dengan Yakobus 2:14-26 mengenai pembenaran oleh iman.